2023
DOI: 10.1001/jamadermatol.2023.1729
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations, Clinical Characteristics, and Prognosis of Patients With Systemic Sclerosis Sine Scleroderma

Abstract: ImportanceSystemic sclerosis (SSc) sine scleroderma (ssSSc) is a subset of SSc defined by the absence of skin fibrosis. Little is known about the natural history and skin manifestations among patients with ssSSc.ObjectiveTo characterize the clinical phenotype of patients with ssSSc compared with patients with limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) within the EUSTAR database.Design, Setting, and ParticipantsThis longitudinal observational cohort study based on the international EUSTAR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Indeed, stratification based on skin induration alone is not sufficient to capture the full spectrum of SSc disease [ 2 ]. Recently, other data from the EUSTAR cohort demonstrated that patients with sine scleroderma SSc may have as high a disease burden as patients with skin involvement [ 64 ]. Further studies are required to enhance our understanding of how gene expression profiles in the skin can be effectively translated into clinical practice, ultimately leading to improved management of SSc patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, stratification based on skin induration alone is not sufficient to capture the full spectrum of SSc disease [ 2 ]. Recently, other data from the EUSTAR cohort demonstrated that patients with sine scleroderma SSc may have as high a disease burden as patients with skin involvement [ 64 ]. Further studies are required to enhance our understanding of how gene expression profiles in the skin can be effectively translated into clinical practice, ultimately leading to improved management of SSc patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Systemic sclerosis (SSc) or scleroderma is an immune-mediated rheumatic disease characterized by fibrosis of the skin and internal organs and vasculopathy, exhibiting multisystemic pathologies, clinical heterogeneity, a high mortality rate, and extreme morbidity [ 1 ].…”
Section: Introductionmentioning
confidence: 99%